Electrical Properties of Cu-Based Coordination Complexes: Insights from In Situ Impedance Spectroscopy - Jana Pisk; Marko Dunatov; Martina Stojić; Nenad Judaš; Ivica Đilović; Marta Razum; Luka Pavić (Molecules)
This study examines the influence of ligand design on the structural, optical, and electrical properties of copper-based coordination complexes. Ligands H2L1 and H2L2 were synthesized via the reaction of 5-nitrosalicylaldehyde with 2-hydroxy- or 4-hydroxybenzhydrazide. H4L3 was obtained from the reaction of carbohydrazide and salicylaldehyde, while H4L4 was prepared by condensing 4-methoxysalicylaldehyde with thiocarbohydrazide. The research focuses on two key design elements: (1) the effect of hydroxyl group positioning on the aroyl ring in hydrazide ligands (H2L1 vs. H2L2) and (2) the impact of carbonyl versus thiocarbonyl groups and aldehyde substituents in hydrazone ligands (H4L3 vs. H4L4). The resulting complexes, [Cu2(L1)2], [Cu2(L2)2(MeOH)3], [Cu2(L3)(H2O)2], and [Cu2(L4)(H2O)2], were synthesized and characterized using attenuated total reflectance infrared (IR-ATR) spectroscopy, thermogravimetric analysis (TG), and UV-Vis diffuse reflectance spectroscopy. Their electrical properties were investigated using solid-state impedance spectroscopy (IS). The crystal and molecular structure of the complex [Cu2(L2)2(MeOH)3]∙MeOH was determined by single-crystal X-ray diffraction (SCXRD). This study underscores the pivotal role of ligand modifications in modulating the functional properties of coordination complexes, offering valuable insights for the advancement of materials chemistry.